2013
DOI: 10.1530/rep-13-0282
|View full text |Cite
|
Sign up to set email alerts
|

Maternal omega-3 fatty acid intake increases placental labyrinthine antioxidant capacity but does not protect against fetal growth restriction induced by placental ischaemia–reperfusion injury

Abstract: Placental oxidative stress plays a key role in the pathophysiology of several placenta-related disorders. Oxidative stress occurs when excess reactive oxygen species (ROS) damages cellular components, an outcome limited by antioxidant enzymes; mitochondrial uncoupling protein 2 (UCP2) also limits ROS production. We recently reported that maternal dietary omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation reduced placental oxidative damage and enhanced fetal and placental growth in the rats. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…We recently demonstrated that maternal n-3 PUFA supplementation enhanced mRNA expression and activity of major antioxidant enzymes in the placental LZ across the final third of rat pregnancy (Jones et al 2013c), coincident with reduced placental oxidative damage (Jones et al 2013a). These findings are consistent with an in vitro study, in which treatment of placental BeWo cells with modest levels of DHA reduced oxidative DNA damage and increased cell survival when challenged by an oxidative insult (Shoji et al 2009).…”
Section: Omega-3 Fatty Acids and Placental Oxidative Stresssupporting
confidence: 77%
See 1 more Smart Citation
“…We recently demonstrated that maternal n-3 PUFA supplementation enhanced mRNA expression and activity of major antioxidant enzymes in the placental LZ across the final third of rat pregnancy (Jones et al 2013c), coincident with reduced placental oxidative damage (Jones et al 2013a). These findings are consistent with an in vitro study, in which treatment of placental BeWo cells with modest levels of DHA reduced oxidative DNA damage and increased cell survival when challenged by an oxidative insult (Shoji et al 2009).…”
Section: Omega-3 Fatty Acids and Placental Oxidative Stresssupporting
confidence: 77%
“…Similarly, in human placental explants, DHA administration reduced LPS-induced oxidative damage and restored antioxidant capacity (Stark et al 2013). Dietary n-3 PUFAs may also reduce ROS generation, given that they increase Ucp2 mRNA expression in mouse white adipose tissue (Hun et al 1999) R148 M L Jones and others placental tissue, being predominantly expressed by the syncytiotrophoblast (Stark et al 2012), although maternal dietary n-3 PUFA supplementation in the rat did not affect placental Ucp2 mRNA expression in our recent study (Jones et al 2013c). The effect of maternal n-3 PUFA supplementation on oxidative status of the early gestation placenta, and of particular interest during the onset of placental perfusion, is unknown.…”
Section: Omega-3 Fatty Acids and Placental Oxidative Stressmentioning
confidence: 61%
“…In murine models obesity alters placental morphology, cell proliferation and inflammation [44] and maternal diet alters placental gene expression [45] and epigenetic systems [46] in a sexually dimorphic manner. Maternal dietary n-3 polyunsaturated fatty acid administration gave sexually dimorphic changes in gene expression in placentas in mice [47] and in humans [41]. The underlying basis for these sexually dimorphic differences in gene expression in placenta remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…arachidonic acid), plays a major role in inflammation. Moreover, omega‐3 fatty acids increase placental labyrinthine antioxidant capacity. It has been hypothesized that omega‐3 increases fetal growth rate by improving placental blood flow due to a lowered thromboxane/prostacyclin ratio and blood viscosity by correcting the imbalance in vasoactive PG.…”
Section: Discussionmentioning
confidence: 99%